2000
DOI: 10.1097/00000539-200011000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prolonged Low-Flow Sevoflurane Anesthesia on Renal and Hepatic Function

Abstract: During low-flow sevoflurane anesthesia, intake of Compound A reached 277 +/- 120 ppm-h, but the effect on the kidney and the liver was the same in high-flow sevoflurane and low-flow isoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 24 publications
1
25
0
3
Order By: Relevance
“…Although transient nephrotoxicity was demonstrated by Eger et al [19] and Goldberg et al [20] with respectively 80-160 ppm/h and 240 ppm-h of CA exposure in humans, the majority of publications demonstrate no nephrotoxicity in humans with the use of sevoflurane in combination with any kind of absorbent [21][22][23]. The results of this study, together with the results from our laboratory study [9], confirm these observations.…”
Section: Discussionsupporting
confidence: 83%
“…Although transient nephrotoxicity was demonstrated by Eger et al [19] and Goldberg et al [20] with respectively 80-160 ppm/h and 240 ppm-h of CA exposure in humans, the majority of publications demonstrate no nephrotoxicity in humans with the use of sevoflurane in combination with any kind of absorbent [21][22][23]. The results of this study, together with the results from our laboratory study [9], confirm these observations.…”
Section: Discussionsupporting
confidence: 83%
“…A sample size was calculated based on a previous study with reported values for recovery times and on ␤ -and ␣ -values of 0.2 and 0.05, respectively, which suggested that 25 patients would be needed in each group to detect a difference in recovery times of 30% [7] . Normal distribution of the collected data was tested by the Shapiro-Wilk test.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this has been shown to result in more rapid recovery from anesthesia maintained with sevoflurane [6] . Although low-flow anesthesia techniques with inhalation anesthetics were previously reported in adult patients [7] , there is no study in the literature regarding the use of low-flow anesthesia with these agents and remifentanil infusion. We hypothesize that addition of remifentanil to low-flow sevoflurane anesthesia may reduce both the amount of sevoflurane needed and recovery scores.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences between the three groups at any time point after anaesthesia. Despite an average compound A uptake of 277 B 120 ppmWh during low-flow sevoflurane anaesthesia the effect on the kidney was the same as with highflow sevoflurane and low-flow isoflurane anaesthesia [30]. These observations certainly are a strong argument against the existence of a nephrotoxic threshold as proposed by Eger and coworkers.…”
Section: Human Studiesmentioning
confidence: 64%